Research on Carbon Emission Management of Electric Power Enterprises Based on Blockchain Technology - Li Yongliang; Xia Xuwei; Qiao Ning; Zhang Pei; Zhang Jisheng (SHS Web of Conferences, 2023)
As a high energy-consuming industry, it is especially important for electric power companies to manage carbon emissions well. This study analyzes the main problems of electric power companies in carbon asset management, and investigates the methods of intelligent, digital and transparent management of carbon emission situation using intelligent Internet of Things and blockchain technology. Carbon emission management based on blockchain technology can improve the accuracy and openness of carbon asset data and promote electric power companies to move forward to the low-carbon ecological era.